Response Surface Optimization for The Extraction of Oil from Dog Rose Seed (Rosa Canina) - Hasanov, Jahongir Hikmatilloevich; Sharofitdinovich, Nodir Berdiev; Ravshan, Haydarov Vosil; Dilmurotovich, Sherzod Mirzaxmedov; Ismoilovich, Shavkat Salikhov (Teknik Lingkungan Universitas Islam Indonesia, 2022)
Solvent extraction of dog rose seed was conducted to establish best operation conditions for future study. Extraction variables were temperature, solvent type and L/S ratio. The best extraction conditions at laboratory scale were investigated applying Box-Behnken design (BBD) using response surface methodology (RSM). The highest extract yield was obtained (6.93 %) by isopropanol at the optimum conditions of 3 L/S ratio and 50-55 0C temperature range. Results of experiments confirmed the results of prediction.